Assessment of methotrexate hepatotoxicity in psoriasis patients: a prospective evaluation of four serum fibrosis markers - Chládek, J; Simková, M; Vanecková, J; Hroch, M; Vávrová, J; Hůlek, P (Journal of the European Academy of Dermatology and Venereology, 2013)
BACKGROUND: Low-dose oral methotrexate (MTX) is an effective immunosuppressive therapy for chronic plaque psoriasis. However, its use is hampered by the risk of liver fibrosis. AIM: To compare the results of serial measurements of serum fibrosis markers during the remission-induction phase of treatment with MTX to those of patients on biological therapy and long-term MTX therapy (>2 years). SUBJECTS AND METHODS: Serum concentrations of hyaluronic acid, N-terminal propeptide of collagen type III (PIIINP) and the results of two multi-test algorithms Fibrotest and Hepascore were evaluated in patients with chronic plaque psoriasis (N = 24, age: 28-79 years, baseline Psoriasis Area Severity Index PASI 13.5, range 2.2-33) at baseline and weeks 16 and 26 after the start of pharmacokinetically guided therapy with MTX (Group A). Patients on established therapy with biologics (N = 15, Group B) and long-term MTX users (N = 10, Group C) with the mean baseline PASI scores of 0.9 and 1.2 were studied in parallel cohorts. RESULTS: At baseline, HA, Hepascore and PIIINP were correlated with PASI of Group A patients. At weeks 16 and 26, HA decreased by 48% and 40% (P < 0.001) and Hepascore by 31 (P < 0.01) and 20% (P < 0.05) respectively. PASI75 (≥ 75% improvement from baseline PASI) was observed in 76% of Group A patients by week 26 and the absolute decreases in PASI and both fibrosis markers were correlated (HA: r = 0.49, P = 0.018, Hepascore: r = 0.47, P = 0.022). In contrast, no significant within-group differences were found in HA and Hepascore results of patients in the groups B and C. PIIINP and Fibrotest were stable in all groups. CONCLUSION: The fibrosis markers hyaluronic acid and Hepascore (the multiple test algorithm which includes hyaluronic acid) are less liver specific and more prone to reflect psoriasis activity than PIIINP and Fibrotest.
Keywords: senioři; methotrexát; Fibrosis; Middle Aged; mužské pohlaví; Prospective Studies; Adult; Psoriasis; ženské pohlaví; Humans; prospektivní studie; Methotrexate; biologické markery; lidé středního věku; fibróza; dospělí; Biomarkers; Female; Aged; lidé; Male; psoriáza